Cardiovascular disease-specific mortality in 270, 618 patients with non-small cell lung cancer. (1st May 2021) - Sun, Jin-Yu; Zhang, Zhen-Ye; Qu, Qiang; Wang, Ning; Zhang, Yu-Min; Miao, Ling-Feng; Wang, Ji; Wu, Li-Da; Liu, Ying; Zhang, Chang-Ying; Wang, Ru-Xing
Abstract: Background: This study aimed to investigate the trend of cardiovascular disease (CVD)-specific mortality in patients with non-small cell lung cancer (NSCLC) and identify prognostic factors for CVD-specific death in stage NSCLC patients. Methods: In this study, 270, 618 NSCLC patients were collected from the Surveillance, Epidemiology, and End Results database. CVD- and NSCLC-specific cumulative mortality and proportion of death were calculated and graphically displayed to describe the probability of specific endpoints. Prognostic factors for CVD-specific mortality were evaluated by cause-specific hazard ratios (HR) with 95% confidence intervals (CI) using the competing risk model with non-cardiovascular death as competing risks. Results: Among all competing causes of death, lung cancer resulted in the highest cumulative mortality, followed by CVDs and other causes. In the proportion of cause-specific death, heart diseases accounted for approximately 5.3% of the total death, only secondary to primary cancer. In all three stages, higher age, squamous cell carcinoma, and no-or-unknown chemotherapy and/or radiotherapy were associated with a higher risk of CVD-specific death, while surgery treatment seemed to be a protective factor. Female gender was statistically related to CVD-specific death in stage I and III patients with HRs of 0.84 (0.78–0.91) and 0.84 (0.77–0.93), respectively. Interestingly, right-sided laterality was correlated with lower CVD-specific mortality with HR of 0.82 (0.74–0.90) in stage III. Conclusions: This study illustrated the historical trend of CVD-specific death in NSCLC patients and assesses potential prognostic risk factors, highlighting the involvement of cardio-oncology teams in cancer treatment to provide optimal comprehensive care and long-term surveillance for cancer patients. Highlights: Investigate the trend of CVD-specific mortality in patients with NSCLC. Evaluate prognostic factors for CVD-specific death in stage I, II, and III patients. Highlight the importance of cardio-oncology.